2015
DOI: 10.1242/dmm.019208
|View full text |Cite
|
Sign up to set email alerts
|

Clueless, a protein required for mitochondrial function, interacts with the PINK1-Parkin complex in Drosophila

Abstract: Loss of mitochondrial function often leads to neurodegeneration and is thought to be one of the underlying causes of neurodegenerative diseases such as Parkinson's disease (PD). However, the precise events linking mitochondrial dysfunction to neuronal death remain elusive. PTEN-induced putative kinase 1 (PINK1) and Parkin (Park), either of which, when mutated, are responsible for early-onset PD, mark individual mitochondria for destruction at the mitochondrial outer membrane. The specific molecular pathways th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(77 citation statements)
references
References 52 publications
5
72
0
Order By: Relevance
“…The peculiar mitochondrial phenotype had already been observed in adult muscles from the Drosophila clueless strain (Sen et al, 2015) but was absent in COS7 cells in which CLUH expression was silenced using siRNA (Gao et al, 2014), suggesting that stable CLUH-KO clones trigger adaptation processes that are not set in an acute model triggered by siRNA. The existence of two mitochondrial populations in KO cells could be related to the physical and functional interactions between CLUH and the PINKParkin pathway, which promote the turnover of mitochondria to eliminate any that are defective (Cox and Spradling, 2009;Sen et al, 2015;Wang et al, 2016). Indeed, a cross-talk between CLUH and mitophagy in Drosophila was found to be associated with the degradation of the valosin-containing protein Mitofusin (Marf ), in order to prevent the fusion between healthy and altered mitochondria (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The peculiar mitochondrial phenotype had already been observed in adult muscles from the Drosophila clueless strain (Sen et al, 2015) but was absent in COS7 cells in which CLUH expression was silenced using siRNA (Gao et al, 2014), suggesting that stable CLUH-KO clones trigger adaptation processes that are not set in an acute model triggered by siRNA. The existence of two mitochondrial populations in KO cells could be related to the physical and functional interactions between CLUH and the PINKParkin pathway, which promote the turnover of mitochondria to eliminate any that are defective (Cox and Spradling, 2009;Sen et al, 2015;Wang et al, 2016). Indeed, a cross-talk between CLUH and mitophagy in Drosophila was found to be associated with the degradation of the valosin-containing protein Mitofusin (Marf ), in order to prevent the fusion between healthy and altered mitochondria (Wang et al, 2016).…”
Section: Discussionmentioning
confidence: 86%
“…However, in Arabidopsis, mutations in the CLU family gene FRIENDLY do not cause constrictions, but instead lead to increased association time during the mitochondrial fusion process, which was reported to favor clustering (El Zawily et al, 2014). In Drososphila, the CLU ortholog clueless interacts genetically (Cox and Spradling, 2009) and physically with the PINK1-Parkin pathway (Sen et al, 2015), to promote Valosin-Containing Protein (VCP)-mediated Marf degradation during the Parkindependent mitophagy (Wang et al, 2016). More recently, Gao et al have reported that human CLUH interacts with a subset of mRNAs encoding mitochondrial proteins, suggesting that CLUH is also involved in mitochondrial biogenesis (Gao et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since there are many small Clu particles present, it is possible that a larger fraction of mitochondria is associated with particles than we can see using fixed tissue imaging. Clu associates with several mitochondrial outer membrane proteins, including TOM20 and Porin, and also self-associates, however it is unclear how Clu particles associate with mitochondria (6). Attempts to simultaneously visualize mitochondria and Clu particles live have been stymied by follicle sensitivity to TMRE addition (the Clu particles disperse), though there is evidence that Clu particles in Arabidopsis do move with mitochondria (12).…”
Section: Drosophila Clu and Vertebrate Cluh Are Ribonucleoproteins Anmentioning
confidence: 99%
“…Female germ cells have been an excellent tissue in which to study Clu particles as they are highly metabolically active, are very large and have a large number of particles (Kato and Nakamura, 2012). In order to better understand Clu's role in the cell, we used live-imaging to dissect Clu particle dynamics and whether it recapitulates our previous observations in fixed tissues (Cox and Spradling, 2009;Sen et al, 2015). To do this, we imaged Clu-GFP in the GFP trap line clueless CA06604 (Buszczak et al, 2007).…”
Section: Clu Particles Are Abundant and Highly Dynamicmentioning
confidence: 99%
See 1 more Smart Citation